Fearful and Faint-Hearted: On Affect and the Just-War Tradition - Kavka, Martin (Journal of religious ethics, 2023)
In the spirit of this group of articles commemorating the fiftieth anniversary of the Journal of Religious Ethics, dealing with tradition-based reasoning, this article takes up a passage from Deuteronomy 20 that allows the “fearful and faint-hearted” person not to participate in battle, as well as the rabbinic and medieval appropriations of this passage in the Jewish tradition. It argues that this verse gives primacy to affect in a way that complicates standard interpretations of the Jewish tradition on just war and allows us to see the pliability of tradition. Finally, the article argues that scholars assessing the justice of conflicts need to attend to the circulation of affects in a reasoning community, as is currently happening on scholarship on moral injury.